Pemarkah Kesantunan Linguistik Tuturan Bahasa Jepang Staf Hotel di Bali - Kusumarini, Indah (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
Services in the hotel industry are generally formal. The asymmetric relationship between the service buyer and the service provider has implications for the hotel's procedures in providing services to guests, such as maintaining of courtecy and polite speech. Based on the results of data analysis of conversations between Japanese guests and hotel staff in Bali, several verbal politeness markers in hospitality services have been found, they are; modality (1) “ please”, (2) “would you please”, (3)